Mental health, serum biomarkers and survival in severe COPD: a pilot study. Issue 1 (December 2015) - Zilz, Christian; Blaas, Stefan; Pfeifer, Michael; Jörres, Rudolf; Budweiser, Stephan
Abstract Background Chronic obstructive pulmonary disease (COPD) impairs physical status and impacts on mental health. This prospective study was designed to assess associations between mental health and systemic biomarkers, and their combined relationship with long-term survival in stable severe COPD. Methods Forty-five patients with severe but stable COPD (forced expiratory volume in 1 s of 29.8 (quartiles: 22.6; 41.4) %predicted) were assessed using the Hospital Anxiety and Depression Scale (HADS), the Patient Health Questionnaire (PHQ), St. George's Respiratory Questionnaire and the State-Trait Anxiety Inventory (STAI). The following serum biomarkers were measured: 25-OH-cholecalciferol, C-reactive protein, erythrocyte sedimentation rate, leucocyte number, serum amyloid-A (SA-A), N-terminal pro-brain natriuretic peptide, troponin I, glycosylated haemoglobin, haemoglobin (Hb), haematocrit (Hc), creatinine and thyroid-stimulating hormone. Patients were followed-up for 36 months. Associations between aspects of mental health and biomarkers, and their utility as predictors of 3-year survival were evaluated by regression analyses. Results The prevalence of anxiety (HADS-A: 89.9 %), depression (HADS-D: 58.8 %; PHQ: 60.6 %), somatisation (PHQ-15: 81.8 %) and psychosocial stress (PHQ-stress: 60.6 %) was high. There was a significant positive association between the leucocyte count and SA-A level with STAI-trait anxiety (p = 0.03 andp = 0.005, respectively), and between leucocytes and PHQ-stress (p = 0.043). Hb and Hc were significantly negatively associated with HADS-depression (p = 0.041 andp = 0.031, respectively). Univariate Cox regression analyses revealed that leucocyte count (hazard ratio (HR) 2.976, 95 % CI 1.059-8.358;p = 0.038), and stress (HR 4.922, 95 % CI 1.06–22.848;p = 0.042) were linked to long-term survival. In multivariate Cox regression analyses, including known risk factors for survival in COPD, PHQ-stress (HR 45.63, 95 % CI 1.72–1, 208.48;p = 0.022) remained significantly associated with survival. Conclusion In this pilot study different dimensions of mental health were correlated to serum biomarkers, probably reflecting systemic effects of COPD. While leucocyte number and PHQ-stress were associated with long-term survival in univariate analyses, PHQ-stress remained in multivariate analyses as independent prognostic factor.